Retinal thickness and vascular density changes in Keratoconus: A systematic review and meta-analysis - Hadi Vahedi; Mirsaeed Abdollahi; Reza Moshfeghinia; Shima Emami; Navid Sobhi; Rana Sorkhabi; Ali Jafarizadeh (Heliyon)
Purpose: This systematic review and meta-analysis aimed to assess the changes in retinal layer thickness and vascular density in patients diagnosed with keratoconus (KC). Methods: We conducted a thorough search in PubMed, Scopus, Embase, and Web of Science, encompassing all observational studies from January 1990 to February 2024. We analyzed the data using STATA software 17 and the random effects model with the restricted maximum likelihood (REML) or maximum likelihood (ML) method to pool the standardized mean difference (SMD) and the weighted mean difference (WMD) of retinal thickness and vascular density compared to non-KC eyes. Results: From 4608 records, 16 primary studies met our inclusion criteria, involving 1932 eyes in two groups. The meta-analysis revealed a significant reduction in retinal nerve fiber layer (RNFL) thickness (SMD: −0.30 [-0.52, −0.08]), perifoveal macular thickness in the nasal region (SMD: −0.32 [-0.55, −0.09]) and superior region (SMD: −0.24 [-0.47, −0.02]), and superior capillary plexus (SCP) density (SMD: −1.52 [-2.27, −0.77]) of KC eyes. Additionally, there was a mildly to moderately significant increase in the optic nerve head (ONH) disk area (SMD: 0.40 [0.06, 0.75]). However, there were no significant changes in foveal macular thickness, parafoveal macular thickness, or deep capillary plexus (DCP) density. Conclusion: In KC patients, significant alterations in retinal structure and vascular density have been observed. Although these changes do not currently influence treatment strategies, they offer valuable insights into the relationship between the retina and the cornea. Understanding these changes may be essential for future research focused on early detection, potential prognosis markers, and further exploration of the retina-corneal connection in KC.